Risk of low levels of blood group antibodies mediating hemolysis in ABO-incompatible neonates with negative three hemolysis tests - Lin, Hongxing; Luo, Pingxiang; Liu, Chen; Lin, Xiaosong; Que, Chengwen; Zhong, Wenhui (Frontiers in Pediatrics, 2024)
Objective: To explore the risk of low-level blood group antibody-mediated hemolysis in ABO-incompatible newborns with negative three hemolysis tests, aiming to assist in the identification and management of neonatal jaundice.A retrospective case-control study was performed in 892 children with jaundice.The patients were divided into three groups: group I, ABO compatible, negative three hemolysis tests; group II, ABO incompatible, negative three hemolysis tests; and group III, ABO incompatible, positive three hemolysis tests. We analyzed the differences in clinical data, blood routine and biochemical laboratory results.Results: 1) Patients in group II had higher levels of mean corpuscular volume (MCV), standard deviation of red blood cell volume distribution width (RDW-SD), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and bile acid (BA) than those in group I (P < 0.05). However, there were no statistically significant differences in the MCV, ALT, ALP and BA levels between groups II and III (P > 0.05). 2) Mean corpuscular hemoglobin concentration (MCHC) > 359.5g/L, cell volume distribution width (RDW-CV) > 15.95%, and reticulocyte count (RET) > 4.235% were identified as independent predictors of positive hemolysis test results (P<0.001). The combination of MCHC, RDW-CV, and RET% yielded an AUC of 0.841.Low-level blood group antibody-mediated hemolysis may occur in ABO-incompatible neonates even when three hemolysis tests are negative. Changes in liver function parameters must be monitored. The combination of MCHC, RDW-CV, and RET% can be used to improve the detection rate of HDN. Keywords: ABO hemolytic disease of the newborn, blood group antibodies, three hemolysis tests, mean corpuscular hemoglobin concentration, coefficient of variation of red blood cell volume distribution width, reticulocyte percentage